Self-degradable prefabricated gel particles for temporary blocking and diversion, preparation method and application thereof
By adopting self -degradation prefabricated gel particles, the existing temporarily blocking steering agent in terms of blocking effect, degradation and environmental friendship, realizing the effect of stable sealing and degrading by itself in high temperature environments, reducing the right right pair Damage damage.
Patent Information
- Application Number
- CN202410686968.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing temporary blocking steering agents have shortcomings in terms of sealing effect, degradability, environmental friendliness and economic applicability. For example, the difficulty of blocking the fiber temporary blocking agent is difficult, and the resistance to temperature and salt resistance is poor. The temporary blocking agent of gel There are hidden dangers of environmental pollution and poor economic applicability, and the particle temporary blocking agent has poor sealing effect, incomplete degradation and great harm to the reservoir.
Adopt a temporary blocking steering with a self-degradable prefabricated gel particles, which consists of a rigidaldehyde resin, N, N, N-dihydrocylite, acrylic hydroxyl ethyl, and cross-linked agent, etc. The merger is solidified under the conditions of 90 to 150 ° C, forming a gel particles that can exist stable in high temperature environments and degrade themselves within a certain period of time.
The temporary steering agent still has a good blocking effect in the environment of 150 ° C. At the same time, it is small to damage the strata. It can degrade itself at high temperature environments. After degradation, it is aquatic solution without harming the storage layer of the oil.
Smart Images

Figure CN118546311B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, and in particular to self-degradable prefabricated gel particles for temporary plugging and diversion, and a preparation method and application thereof. Background Art
[0002] Temporary plugging and diversion fracturing technology is an effective method to increase the productivity of oil and gas wells. It plugs the perforations and reservoir fractures by pumping temporary plugging and diversion agents into the ground to increase the net pressure in the fractures, forcing new fractures to start and divert to extend to unaffected areas, thereby achieving the purpose of expanding the productivity of oil and gas wells. At present, temporary plugging and diversion fracturing technology has been widely used in the production of high-potential old wells and low-productivity new wells. The core of temporary plugging and diversion technology is the selection of temporary plugging agents. At present, the temporary plugging and diversion agents commonly used in oil fields mainly include granular temporary plugging and diversion agents, fiber temporary plugging and diversion agents, and gel temporary plugging and diversion agents.
[0003] Fiber temporary plugging diversion agents are easy to dissolve and flow back during the plugging process and have little damage to the reservoir, but they have problems such as difficulty in bridging plugging and poor resistance to temperature and salt. Gel temporary plugging agents have high plugging strength, high plugging efficiency, and little damage to the reservoir, but they have problems such as potential environmental pollution and poor economic applicability. Granular temporary plugging diversion agents are widely used in plugging technology because of their simple construction process, high compressive strength and strong applicability. However, most of the current granular temporary plugging diversion agents need to fill cracks with rigid particles to complete the plugging. There are pores between particles and it is impossible to form a sealed plugging section. There are problems such as poor plugging effect, incomplete degradation, and great damage to the reservoir.
[0004] The Chinese invention patent with publication number CN117143580A discloses a method for preparing a pre-crosslinked polymer water-swelled material and temporary plugging agent particles. The preparation steps of the gel particles are complicated, the temperature resistance is poor, and the structure is easily destroyed and degraded under high temperature environment, resulting in poor plugging performance. The Chinese invention patent with publication number CN116239721A discloses a method for preparing water-based elastic gel particles. The gel particle system can only be degraded under the action of a breaker, and there are problems such as difficult to control the breaking time, a large amount of residue in the formation after breaking, and easy to cause secondary damage to the formation. Summary of the invention
[0005] In order to solve the above problems, one object of the present invention is to provide a self-degradable prefabricated gel particle for temporary plugging and diversion.
[0006] Another object of the present invention is to provide a method for preparing self-degradable prefabricated gel particles for temporary plugging and diverting, which has reliable principle, simple operation, cheap and readily available raw materials, and controllable preparation process.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0008] The invention discloses self-degradable prefabricated gel particles for temporary plugging and steering. The particles are prepared by reacting and associating the following raw materials at 50-60 DEG C and then curing them at 90-150 DEG C, according to weight percentage: 25.2-35.5% of urea-formaldehyde resin, 34.2-49.9% of N,N-dimethylacrylamide, 10.5-20.9% of hydroxyethyl acrylate, 1.5-2.5% of a crosslinking agent, 0.2-1.3% of an initiator, and the balance is water.
[0009] Furthermore, the cross-linking agent is one of borax and boric acid.
[0010] Furthermore, the initiator is one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0011] A method for preparing self-degradable prefabricated gel particles for temporary plugging and steering, which is used to prepare the self-degradable prefabricated gel particles for temporary plugging and steering, comprises the following steps:
[0012] A1. Add a formulated amount of water into a container, add urea-formaldehyde resin, N,N-dimethylacrylamide, and hydroxyethyl acrylate into the container respectively, and stir until completely dissolved to obtain a reaction solution;
[0013] A2. Add the crosslinking agent into the container and stir for 30 minutes at a stirring speed of 400-800 r / min;
[0014] A3, adding an initiator to a container, introducing an inert gas (such as nitrogen or helium) to remove oxygen from the reaction solution, and after sufficient reaction in the container at a temperature of 50 to 60° C., placing the container in water and cooling it to room temperature to obtain a bulk gel;
[0015] A4. Place the gel generated by the reaction in a constant temperature oven at 90-150°C and solidify for 2-6 hours before taking it out;
[0016] A5, breaking the gel to obtain gel particles, the specific size of the particles is determined according to needs, and can be nanometer, millimeter or centimeter size;
[0017] A self-degradable prefabricated gel particle for temporary plugging and diversion is used in oil and gas reservoirs. When the temperature of the oil and gas reservoir is 90-150°C, the temporary plugging and diversion agent can be solidified within 2-6 hours; when the temperature is 90-150°C, there is no need to add degradation liquid, and the gel particles can be completely degraded within 1-32 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The prefabricated gel particles of the present invention have good temperature resistance and still have a good plugging effect under a 150°C environment.
[0020] (2) The self-degradable prefabricated gel particles for temporary plugging and diversion have little damage to the formation, can enter tiny cracks, and have excellent injection performance.
[0021] (3) The self-degradable prefabricated gel particles for temporary plugging and diverting prepared by the present invention have a simple preparation process, good water absorption and swelling properties, and good viscoelasticity.
[0022] (4) After solidification, the self-degradable prefabricated gel particles for temporary plugging and diversion will absorb water again and swell into gel when encountering water, and spontaneously aggregate to form a tight plugging section.
[0023] (5) The self-degradable prefabricated gel particles for temporary plugging and diversion can be self-degraded in a certain period of time without the need for a degelling agent under an environment of 90 to 150°C. After degradation, they become an aqueous solution, which is friendly to the formation and will not cause damage to the oil reservoir. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical picture of the gel state of Example 4;
[0025] Figure 2 This is a physical picture of the gel particles of Example 4;
[0026] Figure 3 This is a physical picture of the gel particles mixed with clean water in Example 4;
[0027] Figure 4 This is a physical picture of the gel particles in Example 4 absorbing water and swelling into elastic gel;
[0028] Figure 5 This is a physical picture of the gel particles after degradation in Example 4;
[0029] Figure 6 This is a diagram of the stretching recovery experiment of the self-degradable prefabricated gel particles for temporary plugging and diverting in Example 4. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] In actual use, the system components can be appropriately adjusted according to the well conditions, well type, formation water quality, etc.
[0032] Example 1
[0033] 14.1g of water, 35.2g of urea-formaldehyde resin, 34.2g of N,N-dimethylacrylamide, and 14.6g of hydroxyethyl acrylate were respectively added to a 500ml three-necked flask. After they were completely dissolved at a stirring speed of 400r / min, 1.6g of borax was added to the three-necked flask and stirred for 30min until they were completely dissolved. Subsequently, 0.3g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60°C water bath to react for 2h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0034] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in an oven at 150°C for 2h to cure, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in an oven at 150°C, and it can be completely degraded within 6 hours.
[0035] Example 2
[0036] 12.3 g of water, 32.7 g of urea-formaldehyde resin, 37.2 g of N,N-dimethylacrylamide, and 16.1 g of hydroxyethyl acrylate were added to a 500 ml three-necked flask respectively. After they were completely dissolved at a stirring speed of 400 r / min, 1.6 g of borax was added to the three-necked flask and stirred for 30 min until they were completely dissolved. Subsequently, 0.3 g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60° C. water bath to react for 2 h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0037] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in an oven at 150°C for 2h to solidify, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in an oven at 150°C, and it can be completely degraded within 7 hours.
[0038] Example 3
[0039] 11.7 g of water, 30.4 g of urea-formaldehyde resin, 40.8 g of N,N-dimethylacrylamide, and 15.4 g of hydroxyethyl acrylate were respectively added to a 500 ml three-necked flask. After they were completely dissolved at a stirring speed of 400 r / min, 1.5 g of borax was added to the three-necked flask and stirred for 30 min until they were completely dissolved. Subsequently, 0.2 g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60° C. water bath to react for 2 h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0040] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in an oven at 120℃ for 4h to cure, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in an oven at 120℃, and it can be completely degraded within 15 hours.
[0041] Example 4
[0042] 9.5 g of water, 28.6 g of urea-formaldehyde resin, 43.2 g of N,N-dimethylacrylamide, and 16.8 g of hydroxyethyl acrylate were added to a 500 ml three-necked flask respectively. After they were completely dissolved at a stirring speed of 400 r / min, 1.6 g of borax was added to the three-necked flask and stirred for 30 min until they were completely dissolved. Subsequently, 0.3 g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60° C. water bath to react for 2 h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0043] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in an oven at 120℃ for 4h to cure, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in an oven at 120℃, and it can be completely degraded within 17 hours.
[0044] Example 5
[0045] 7.3 g of water, 26.8 g of urea-formaldehyde resin, 47.3 g of N,N-dimethylacrylamide, and 16.9 g of hydroxyethyl acrylate were added to a 500 ml three-necked flask respectively. After they were completely dissolved at a stirring speed of 400 r / min, 1.5 g of borax was added to the three-necked flask and stirred for 30 min until they were completely dissolved. Subsequently, 0.2 g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60° C. water bath to react for 2 h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0046] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in a 90℃ oven for curing for 6h, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in a 90℃ oven, and it can be completely degraded within 25 hours.
[0047] Example 6
[0048] 7.3 g of water, 25.2 g of urea-formaldehyde resin, 49.2 g of N,N-dimethylacrylamide, and 16.5 g of hydroxyethyl acrylate were added to a 500 ml three-necked flask respectively. After they were completely dissolved at a stirring speed of 400 r / min, 1.5 g of borax was added to the three-necked flask and stirred for 30 min until they were completely dissolved. Subsequently, 0.3 g of ammonium persulfate was added to the three-necked flask, nitrogen was introduced to remove oxygen in the reaction solution, and then the three-necked flask was placed in a 60° C. water bath to react for 2 h. After the container was fully reacted to generate a gel, the container was placed in water and cooled to room temperature to obtain a gel aqueous solution.
[0049] Weigh 10g of gel aqueous solution into an ampoule, place the ampoule in an aging tank and place it in a 90℃ oven for curing for 6h, then crush it to obtain gel particles. Then put the gel particles and a small amount of clean water into the ampoule, place it in a 90℃ oven, and it can be completely degraded within 28 hours.
[0050] Comparative Example 1
[0051] The ammonium persulfate in Example 4 was replaced by ammonium chloride, and the other components, amounts and reaction conditions were consistent with those in Example 4.
[0052] When the solidified gel particles were placed at 120°C, the degradation rate was 78.3% within 24 hours.
[0053] Comparative Example 2
[0054] The N,N-dimethylacrylamide in Example 4 was replaced by N-vinylpyrrolidone, and the other components, amounts and reaction conditions were consistent with those in Example 4.
[0055] When the solidified gel particles were placed at 120°C, the degradation rate was 43.5% within 24 hours.
[0056] Test Example 1
[0057] The morphology of the gel temporary plugging agent after reaction into gel in Experimental Example 4 is shown in Figure 1 .
[0058] Test Example 2
[0059] The self-degradability of the gel particles prepared in Experimental Example 4 was tested. After drying the gel, it was crushed to obtain a batch of dry gel particles, such as Figure 2 As shown. Put the gel particles and a small amount of water into an ampoule, as shown Figure 3 As shown. Put the ampoule into the aging tank, place it in a 120℃ oven, take it out after 1 hour, and the gel particles absorb water and expand into gel, as shown Figure 4 As shown. Continue to put it in the oven, the actual picture after degradation is shown in Figure 5As can be seen from the figure, the viscosity of the liquid after degradation is low, and there is no residue left after degradation. Therefore, it is very easy to flow back in the formation without causing damage to the formation.
[0060] Test Example 3
[0061] A gel solution was prepared according to the recipe in Example 4, and placed in a 120° C. constant temperature oven for curing for 2 h. Figure 6 As shown in the figure, the gel particles are stretched. As can be seen from the figure, the gel particles have good viscoelasticity.
[0062] Test Example 4
[0063] Gel particles were prepared according to the formula in Example 4. 1 g of gel particles were loaded into a filter bag. The filter bag was soaked in clean water for 1 day. The bag was taken out and filtered, and the surface moisture of the gel particles was dried. The mass of the gel particles after soaking was weighed, and the water absorption rate of the gel particles was calculated to be 7.3 times.
[0064] Test Example 5
[0065] Degradation performance test, using the gel particle formulations of Examples 1 to 6 as research objects, respectively denoted as 1# to 6#, 10 g of the solidified gel particles were added to an ampoule bottle, placed under conditions of 90 to 150° C., and the mass retention rate of the gel particles was examined. The experimental results are shown in Table 1.
[0066] Table 1 Degradation performance of gel particles in different systems
[0067]
[0068] Test Example 6
[0069] The gel particle formulations of Examples 1 to 6 were used as the research objects, which were recorded as 1# to 6#, respectively. A metal rock plate with a thickness of 1 mm was installed in the crack mold, and then the crack mold was placed in a clamp, connected to the pipeline, and heated to the same curing temperature as in Examples 1 to 6; a mixture of self-degradable prefabricated gel particles and 0.5% guar gum aqueous solution for temporary plugging and diversion was injected at a rate of 1 mL / min. After the pressure was stabilized for half an hour, the permeability k1 after plugging was calculated according to Darcy's law, as shown in Table 2. The crack molds were placed at a constant temperature of 90 to 150°C, and after they were fully degraded, 0.5% guar gum aqueous solution was injected into the crack mold again at 1 mL / min to displace the permeability k2 after degradation, as shown in Table 2.
[0070] Table 2 Blockage rate of gel particles in different systems
[0071]
[0072] The results show that the plugging rates of Examples 1 to 6 before degradation were all higher than 99%, while the plugging rates after degradation were all lower than 1%, which indicates that the self-degradable prefabricated gel particles for temporary plugging have excellent plugging and degradation properties.
[0073] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A self-degradable prefabricated gel particle for temporary blocking and diversion, characterized in that: According to weight percentage, the raw materials including the following components react and associate with each other at 50-60° C., and then solidify at 90-150° C. to obtain: 25.2-35.5% of urea-formaldehyde resin, 34.2-49.9% of N,N-dimethylacrylamide, 10.5-20.9% of hydroxyethyl acrylate, 1.5-2.5% of a crosslinking agent, 0.2-1.3% of an initiator, and the balance is water; The cross-linking agent is one of borax and boric acid; The initiator is one of ammonium persulfate, sodium persulfate and potassium persulfate.
2. A method for preparing self-degradable prefabricated gel particles for temporary plugging and steering, used for preparing the self-degradable prefabricated gel particles for temporary plugging and steering according to claim 1, characterized in that: The steps include: A1. Add a formulated amount of water into a container, add urea-formaldehyde resin, N,N-dimethylacrylamide, and hydroxyethyl acrylate into the container respectively, and stir until completely dissolved to obtain a reaction solution; A2. Add the crosslinking agent into the container and stir for 30 minutes at a stirring speed of 400-800 r / min; A3, adding an initiator to a container, passing an inert gas to remove oxygen in the reaction solution, and after sufficient reaction in the container at a temperature of 50-60°C, placing the container in water and cooling it to room temperature to obtain a bulk gel; A4. Place the gel generated by the reaction in a constant temperature oven at 90-150°C and solidify for 2-6 hours before taking it out; A5. Crush the gel to obtain gel particles.
3. Application of self-degradable prefabricated gel particles for temporary plugging and diversion in oil and gas reservoirs, wherein the self-degradable prefabricated gel particles for temporary plugging and diversion are the self-degradable prefabricated gel particles for temporary plugging and diversion according to claim 1. When the temperature of the oil and gas reservoir is 90-150°C, the self-degradable prefabricated gel particles for temporary plugging and diversion solidify within 2-6 hours; when the temperature is 90-150°C, there is no need to add degradation liquid, and the gel particles are completely degraded within 1-32 hours.
Citation Information
Patent Citations
Water-based elastic gel particles, oil displacement material and preparation method of water-based elastic gel particles and oil displacement material
CN116239721A
Preparation method of pre-crosslinked polymer water-swellable material and temporary plugging agent particles
CN117143580A
Temporary plugging diverting agent used for reservoir reformation, and preparation method thereof
CN106867487A
In-slot temporary plugging agent for fracturing and preparation method thereof
CN109294542A